Benefits and wages: OECD indicators - Organisation for Economic Co-operation and Development (Paris, France : OECD, 2002)
Comparative analyses (with tables) of tax and unemployment benefits in OECD countries.
"OECD indicators."
Some issues available online via SourceOECD.
Issued also in French as: Prestations et salaires - Les indicateurs de l'OCDE.
Keywords: Manpower policy -- OECD countries; Labor supply -- Effect of taxation on -- OECD countries -- Periodicals; Taxation -- OECD countries; OECD countries Periodicals